2016
DOI: 10.18632/oncotarget.8124
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive prostate cancer detection by measuring miRNA variants (isomiRs) in urine extracellular vesicles

Abstract: In many cancer types, the expression and function of ∼22 nucleotide-long microRNAs (miRNA) is deregulated. Mature miRNAs can be stably detected in extracellular vesicles (EVs) in biofluids, therefore they are considered to have great potential as biomarkers. In the present study, we investigated whether miRNAs have a distinct expression pattern in urine-EVs of prostate cancer (PCa) patients compared to control males. By next generation sequencing, we determined the miRNA expression in a discovery cohort of 4 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
120
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(125 citation statements)
references
References 44 publications
3
120
0
2
Order By: Relevance
“…Downregulation of RECK and loss of BTG2 mediated by miR-21 was shown to contribute to prostate cell transformation (65,66). Furthermore, miR in prostate cancer tissues and in serum and urine samples of prostate cancer patients was revealed to be an independent diagnostic and prognostic biomarker (67)(68)(69).…”
Section: Mir-21 and Solid Tumorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Downregulation of RECK and loss of BTG2 mediated by miR-21 was shown to contribute to prostate cell transformation (65,66). Furthermore, miR in prostate cancer tissues and in serum and urine samples of prostate cancer patients was revealed to be an independent diagnostic and prognostic biomarker (67)(68)(69).…”
Section: Mir-21 and Solid Tumorsmentioning
confidence: 99%
“…The application of this non-invasive approach may be considered for monitoring responses of lung cancer patients to EGFR-TKI treatment (79). Furthermore, the implication of miR-21 in chemotherapy resistance has been investigated for a wide range of solid cancer types, including pancreatic and prostate cancer, hepatoma, ovarian cancer, glioma, and head and neck, stomach and bladder cancer (Table I) (68)(69)(70)(71)75,(77)(78)(79)(80)(81)(82)(83)(84)(85)(86)(87)(88)(89)(90)(91)(92)(93)(94). These results support the clinical application of miR-21 inhibition in cancer treatments in the future.…”
Section: Mir-21 and Solid Tumorsmentioning
confidence: 99%
“…They are generated from a single miRNA locus through the miRNA processing and maturation process. Koppers-Lalic et al [96] identified that isomiRs of miR-21, miR-375 and miR-204 measured in urinary extracellular vesicles could distinguish control men from PCa patients. The authors found an AUC of 0.821 for these set of isomiRs, meanwhile the AUC corresponding to the mature miRNA was 0.661.…”
Section: Exosomal Biomarkersmentioning
confidence: 99%
“…For instance, in just two weeks of Medline updates we found papers on long non-coding RNAs 52 , ALKBH3 53 , two different approaches to MicroRNAs 54,55 , a surface-enhanced Raman scattering (SERS)-based microdroplet sensor for PSA 56 , urinary carbonic anhydrase IX splicing messenger RNA 57 , prostate specific membrane antigen (PSMA) 58 , and platelet factor-4 (PF-4) 58 . Here we review some of the most prominent recent markers.…”
Section: Other Markersmentioning
confidence: 99%